Characterization of ply bulge failures in truck bus radial tyres - Yadav, Ankush; Jiju, C. M.; Kumar, Prashant; Das, Narayan Chandra (Frontiers in Mechanical Engineering, 2025)
Ply bulge failure in Truck and Bus Radial (TBR) tyres, predominantly observed in the shoulder region, is a critical issue impacting tyre performance and safety. This study investigates the root cause of such failures through a comprehensive analysis of 13 field-return tyres of varying patterns and sizes. A multi-step methodology, including visual inspection, X-ray analysis, shearography, microscopy, FTIR, and adhesion testing, was employed to characterize the failure mechanism. Visual inspection was used to identify external factors such as punctures, overloading, or bead damage, while X-ray analysis confirmed the absence of structural defects, such as cord spacing irregularities or belt offset, indicating that intrinsic material interactions were the primary drivers of failure. Shearography pinpointed incipient separation areas, which were further examined microscopically. Microscopic analysis revealed debonding failure mode at the carcass ply-rubber interface as the primary crack initiation mode, followed by propagation along cord surfaces and then transferring to adjacent cords. To distinguish between rubber degradation and adhesive layer aging, forensic analysis combining FTIR and 90◦ peel test (adhesion test) was conducted. FTIR analysis confirmed the rubber compound’s chemical stability, with no evidence of degradation such as carbonyl group formation or reduction in vinyl and alkene groups. However, the adhesion test revealed reduced adhesion strength, correlating with ply bulge initiation. Sections with no ply bulge initiation exhibited a minimum adhesion strength of 13 kgf/inch, whereas sections with initiation showed a maximum strength of 13 kgf/inch, highlighting adhesive aging as the root cause. This study provides an in-depth understanding of ply bulge failure mechanisms in TBR tyres and establishes methodologies for root cause analysis.